Presentation, management and outcomes of ileoanal pouch cancer: a single‐centre experience. (1st July 2021) - Patel, Roshani; Reza, Lillian; Worley, Guy Henry Thomas; Allison, Lisa; Evans, Samantha; Antoniou, Anthony; Jenkins, John T.; Faiz, Omar D.; Corr, Alison; Clark, Sue K.; von Roon, Alexander; Latchford, Andrew
Abstract: Aim: This study aimed to determine the clinical presentation, management and outcomes for patients with ileoanal pouch cancer. Method: Patients who were diagnosed with ileoanal pouch cancer were identified from our polyposis registry (1978–2019) and operative and referral records (2006–2019). Details of presentation, endoscopic surveillance, cancer staging and management were retrieved from hospital records. Results: Eighteen patients were identified (12 with ulcerative colitis, one with Crohn's disease, three with familial adenomatous polyposis [FAP], two with dual diagnosis of FAP and inflammatory bowel disease). The median time from pouch formation to cancer diagnosis was 16.5 years (range 5–34 years) and the median age of the patient at pouch cancer diagnosis was 54 years (range 35–71 years). Eleven of the 18 patients were undergoing surveillance. Four of five FAP patients developed pouch cancer whilst on surveillance. Eight patients were asymptomatic at the time of pouch cancer diagnosis. Two patients had complete clinical response following chemoradiotherapy. Fourteen patients underwent pouch excision surgery (eight with exenteration). Median survival was 54 months; however, only eight patients had outcomes available beyond 24 months follow‐up. Conclusions: Pouch cancer can occur in patients despite routine surveillance and without symptoms, and survival is poor. Centralization of 'high‐risk' patients who require surveillance is recommended and a low threshold for referral to centres that can provide expert investigation and management is advised.